The Relationship of Leg Muscle Strength and Agility towards Sabit Kickc Tuo Pusako Pencak Silat Athletes - Roviandi, Riri; Maulana, Zeno Triyuzi; Melico, Afdalia (Jurnal Guru Peneliti Professional, 2019)
This research originated from the fact that the low ability of the athletes of the Tuo Pusako Minang Silat in Bukittinggi to perform Sabit kicks. This is thought to be caused by leg muscle strength and agility. For this reason, this study aims to see the relationship between leg muscle strength and agility to the athlete's Sabit kicking ability at the Tuo Pusako Minang Silat. This type of research is correlational. The population in this study were 27 athletes at Tuo Pusako Minang Silat by using a purposive sampling technique, namely taking the sample to only 20 men due to differences in the abilities of men and women. The data analysis technique used is simple and multiple correlation analysis techniques. From the research results obtained are the results of the correlation coefficient rcount> rtable (the research hypothesis is accepted) and testing the significance of the correlation coefficient for the XI and Y variables, the X2 and Y variables obtained Fcount> Ftable values. The results of this study prove that: There is a significant relationship between leg muscle strength and the Sabit kick of the Tuo Pusako Minang Silat athletes.